A case study on written comments as a form of feedback in teacher education: so much to gain. Issue 2 (14th March 2016) - Arts, Jorik Gerardus; Jaspers, Mieke; Joosten-ten Brinke, Desiree
Abstract: In Higher Education, much of a lecturer's time is spent on supplying students with written comments as a form of feedback on assignments. Although it is clear that students use these comments to make adjustments to their assignments, it is doubtful that these comments create a learning effect. This may indicate that the way feedback is supplied and/or the quality of the feedback lacks information for improving future performance. In this case study, written feedback has been analysed and the perception of students on the quality of written feedback in relation to their learning behaviour has been taken into account.